2015
DOI: 10.1124/jpet.115.226993
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Micelle Formulations of Proteasome Inhibitor Carfilzomib for Improved Metabolic Stability and Anticancer Efficacy in Human Multiple Myeloma and Lung Cancer Cell Lines

Abstract: Carfilzomib (CFZ) is a second-generation proteasome inhibitor drug approved for the treatment of multiple myeloma. Contrary to its excellent antimyeloma activity, CFZ has shown only limited efficacy in patients with solid malignancies. This lack of efficacy has been attributed in part to rapid degradation of CFZ in the body, possibly hindering the ability of CFZ to access the proteasome target in solid tumors. We hypothesized that polymer micelles, a currently Food and Drug Administration-approved nanoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 34 publications
1
26
1
Order By: Relevance
“…PNAs are made from biocompatible polymers and small molecule components such as poly(ethylene glycol) (PEG), poly(ethylene imine) (PEI), poly(lysine) (PLL), and palmitic acid (PAL), which are tethered each other through a coupling reaction between a scaffold (PEI or PLL) and grafts (PEG and PAL). In previous studies, we confirmed that PNAs are uniform in shape and size with an average diameter of 30 nm, and they can fine-tune the entrapment and release of various model anticancer drugs in comparison to other FDA-approved injection formulations such as polymer micelles and modified cyclodextrin (2629). PNAs were physically and chemically stable to prevent changes in particle diameter, surface charge, and shape while entrapping various therapeutic and imaging molecules concurrently in the core (21, 22, 27, 3034).…”
Section: Introductionsupporting
confidence: 72%
“…PNAs are made from biocompatible polymers and small molecule components such as poly(ethylene glycol) (PEG), poly(ethylene imine) (PEI), poly(lysine) (PLL), and palmitic acid (PAL), which are tethered each other through a coupling reaction between a scaffold (PEI or PLL) and grafts (PEG and PAL). In previous studies, we confirmed that PNAs are uniform in shape and size with an average diameter of 30 nm, and they can fine-tune the entrapment and release of various model anticancer drugs in comparison to other FDA-approved injection formulations such as polymer micelles and modified cyclodextrin (2629). PNAs were physically and chemically stable to prevent changes in particle diameter, surface charge, and shape while entrapping various therapeutic and imaging molecules concurrently in the core (21, 22, 27, 3034).…”
Section: Introductionsupporting
confidence: 72%
“…Micelles showed improved stability profiles with at least 50% of the active carfilzomib remaining after 20 minutes of incubation in mouse liver homogenates. Micelles were tested in RPMI‐8226 cell line and shown comparable anticancer effect compared with free carfilzomib (Table ). However, this study is very preliminary, only in vitro studies were realized.…”
Section: Nanoparticle Delivery Systems For Myelomamentioning
confidence: 99%
“…The EPR effect is an important factor for delivery of nanoparticle systems in general, which has been confirmed mainly for solid tumors. Although encouraging results have been shown with liposomes, polymeric NPs, micelles, and inorganic NPs using non‐targeted approaches, MM is a hematological malignancy and it is still not clear that the EPR effect will have a role in how non‐targeted NPs exploit passive targeting based on the pathophysiological conditions of the myeloma microenvironment.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of CFZ, we previously reported that several CFZ-loaded PM formulations composed of biodegradable block copolymers poly(ethylene glycol)-poly(caprolactone) (PEG-PCL) displayed improved metabolic stability and anticancer efficacy profiles in vitro [11]. Given these results, the logical next step was to examine whether these in vitro improvements achieved by CFZ-loaded PM formulations would be recapitulated in vivo .…”
Section: Introductionmentioning
confidence: 99%